PSORIASIS ERUPTIONS LIKE SIDE EFFECTS AFTER THE USE ETANERCEPT-CASE REPORT - Veselinović, Mirjana (Medicinski časopis, 2019)
The use  of tumor necrosis factor antagonists (anti-TNF) has become  a usual practice   to  treat various inflammatory diseases. Although indicated for the treatment of psoriasis, anti-TNF may paradoxically trigger a psoriasiform condition. We present a case of a female patient who, during  the use of etanercept for rheumatoid arthritis, developed psoriasis. After  histopathological confirmation and consultation dermatologist concluded that psoriasis is a paradoxical effect of anti-TNF inhibitors. Anti TNF inhibitor is replaced with other biological drug- tocilizumab. After the change of the drug has been a complete resolution of psoriasis eruptions.Paradoxical form of psoriasis after use of anti-TNF inhibitor requires a change of the drug with other mechanism of action.